Digital Transformation Maturity Development For Higher Educationin Developing Country - Bisri Bisri; Achmad Husen; Suparno Suparno (Dinasti International Journal of Education Management And Social Science, 2025)
This study focuses on developing a digital transformation maturity model tailored to higher education in developing countries, with a specific case study on Indonesia. The purpose of this research is to evaluate and enhance the digital strategies of higher education institutions to improve operational efficiency and educational outcomes. Using a thematic literature review and analysis, this study identifies challenges and proposes a structured model for assessing digital maturity. Major findings include the importance of leadership, institutional readiness, and stakeholder collaboration in driving successful digital transformation. This study highlights actionable insights for policymakers and institutions, emphasizing the need for strategic investments in technology and digital literacy.